2014
DOI: 10.1016/j.jcf.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of newborn screening for cystic fibrosis: A simulation study

Abstract: This study suggests that NBS for cystic fibrosis is a cost-effective strategy compared to the absence of NBS. The IRT-PAP newborn screening algorithm with an IRT cutoff at the 96th percentile is the most cost effective NBS approach for Quebec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…The California findings are consistent with those modeled in a cost-effectiveness study of 4 different CF NBS algorithms. 30 However, 2 recent studies 31,32 suggest that IRT/pancreatitis-associated protein algorithms may be even more cost-effective than California's 3-step algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The California findings are consistent with those modeled in a cost-effectiveness study of 4 different CF NBS algorithms. 30 However, 2 recent studies 31,32 suggest that IRT/pancreatitis-associated protein algorithms may be even more cost-effective than California's 3-step algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…A more favourable CER of IRT-DNA was observed earlier [9], but we included more cost elements (organisation of CF-screening, genetic counselling) and had higher cost estimates. A recent simulation study also showed that IRT-PAP is the most cost-effective strategy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of our comprehensive, longitudinal study is informing estimates for future cost‐effectiveness studies involving CF populations. The annual cost of care by age‐range, types of care, clinical risk factors, and utilization class, and the uncertainty of the estimates can all be used in conjunction with distributional assumptions to account for uncertainty in economic evaluations of newborn screening and relatively new therapies, such as dornase and CFTR modulator therapy …”
Section: Discussionmentioning
confidence: 99%